2019
DOI: 10.1002/bies.201900103
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Intravascular Schistosomes Coat Themselves in Glycolytic Enzymes?

Abstract: Schistosomes are intravascular parasitic helminths (blood flukes) that infect more than 200 million people globally. Proteomic analysis of the tegument (skin) of these worms has revealed the surprising presence of glycolytic enzymes on the parasite's external surface. Immunolocalization data as well as enzyme activity displayed by live worms confirm that functional glycolytic enzymes are indeed expressed at the host-parasite interface. Since these enzymes are traditionally considered to function intracellularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…While glycolysis is a conserved biochemical pathway that takes place in the cytosol of cells, several enzymes that drive this pathway have been reported to be present at the schistosome surface following proteomic analysis (reviewed by Pirovich et al, 2019). The glycolytic enzymes enolase and GAPDH were both identified as schistosome surface proteins in ten of 11 independent schistosome tegumental proteomic studies (Pirovich et al, 2019). No other glycolytic enzymes were found more frequently in the schistosome tegumentome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While glycolysis is a conserved biochemical pathway that takes place in the cytosol of cells, several enzymes that drive this pathway have been reported to be present at the schistosome surface following proteomic analysis (reviewed by Pirovich et al, 2019). The glycolytic enzymes enolase and GAPDH were both identified as schistosome surface proteins in ten of 11 independent schistosome tegumental proteomic studies (Pirovich et al, 2019). No other glycolytic enzymes were found more frequently in the schistosome tegumentome.…”
Section: Discussionmentioning
confidence: 99%
“…Is there any selective advantage for the parasites to express the protein in this location? In schistosomes, and in other systems, evidence is accumulating that extracellular glycolytic enzymes like GAPDH can be engaged in non-traditional, nonglycolytic or 'moonlighting' functions relating, for example, to immune modulation and/or blood clot dissolution (Karkowska-Kuleta and Kozik, 2014;Pirovich et al, 2019;Sirover, 2017). We previously showed that live intravascular schistosomes could promote PLMG activation in the presence of tPA (Figueiredo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being widely distributed inside cells, in several instances aldolase has been reported ( Gómez-Arreaza et al, 2014 ; Shams et al, 2014 ; Pirovich et al, 2019 ) to be found on a cell’s exterior membranes, including on the host-exposed surface of many pathogenic organisms (both bacteria and eukaryotic parasites). One of the notable mysteries in the study of moonlighting proteins is that many surface-localized proteins, including aldolase, lack transmembrane domains and signal peptides involved in canonical secretion pathways: bioinformatics analysis of 22 published studies on bacterial surface proteomes revealed that >1,000 of 3,619 proteins found on the cell surface lack such domains ( Wang and Jeffery 2016 ).…”
Section: Evidence For Surface Localization Of Aldolase On Many Pathogensmentioning
confidence: 99%
“…Figure 2 lists the wide variety of organisms that have been demonstrated to possess an extracellular aldolase (left) and instances in which the enzyme has been shown to bind to plasminogen, promoting its activation (right). Pathogens have been reported to use a number of other glycolytic enzymes, including triosephosphate isomerase (TPI), GAPDH, phosphoglycerate mutase (PGM) and enolase, to bind and activate plasminogen ( Pirovich et al, 2019 ; Pirovich et al, 2020 ).…”
Section: Moonlighting Functions Of Aldolase To Aid Pathogen Survivalmentioning
confidence: 99%
“…Glyceraldehyde 3-phosphate dehydrogenase (G3PDH) is a cytosolic antigen. Yet, it was readily detected on the surface of S. mansoni 3 h in vitro schistosomula (Goudot-Crozel et al 1989), lung-stage schistosomula (Tallima and El Ridi 2008;Pirovich et al 2019Pirovich et al , 2020, among adult worms surface membrane-associated molecules, and in larval and adult worms excretory-secretory products (ESP) Sotillo et al 2015). Indeed, schistosome G3PDH (SG3PDH) is considered a prominent moonlighting protein.…”
Section: Glyceraldehyde 3-phosphate Dehydrogenasementioning
confidence: 99%